Knowledge Management Initiatives at Human Resources Development Center at Ministry of Energy and Mineral Resources - Susilo, Joko; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2017)
Abstract. The Human Resources Development Center of Oil and Gas have a duty to carry out human resource development in the oil and gas sector. One of the very important energy sectors in Indonesia is an oil and natural gas. The management is good against this sector will give to the progress of Indonesia. In the current situation, the quality of Human Resource Development Centre of Oil and Gas declined. There is caused by lack of knowledge management activities, regeneration of lecturers and no activity that accommodates the activities of process knowledge management knowledge sharing activities i.e. mainly between senior and junior, as well as the exchange of knowledge with the workers in the oil and gas industry. This research aims to make a proposal for the design of the implementation model of Knowledge Management (KM) on the lecturers and instructors in Human Resource Development Centre of Oil and Gas. The method used is the study of literature, perform data collection through surveys, and interviews. The proposed design of the implementation model KM will be developed with an emphasis on communication as well as the selection of appropriate technologies so that the implementation of this model of KM will be capable of accommodating knowledge sharing. The important point is the success of the application of KM is the existence of communication as well as a strong leadership skill. It is recommended that this model developed in harmony with the company's strategy in achieving the goals and objectives of the OrganizationKeywords: Knowledge Management Systems, Knowledge Sharing, Communication, Technologies